White-Matter Hyperintensities and Cognitive Decline in Late-Life Depression: A Longitudinal Neuroimaging Study in Medan, Indonesia - Taryudi Suharyana; Jason Willmare; Despian Januandri; Brenda Jaleel; Wisnu Wardhana Putra (Scientia Psychiatrica, 2025)
Introduction: Late-life depression (LLD) is often associated with cognitive impairment and structural brain changes, particularly white-matter hyperintensities (WMH). This longitudinal study investigated the relationship between WMH burden, cognitive decline, and depressive symptoms in a cohort of older adults with LLD in Medan, Indonesia. Methods: A prospective, longitudinal study was conducted with 120 participants aged 60 years and older. Participants underwent baseline and 3-year follow-up assessments, including structural MRI, neuropsychological testing, and depression severity. Statistical analyses included mixed-effects models to examine longitudinal changes and correlations. Results: At baseline, the LLD group exhibited significantly higher WMH volume compared to controls (p < 0.001). Over the 3-year follow-up, the LLD group showed a significantly greater increase in WMH volume (average increase of 0.4 Fazekas points) compared to controls (average increase of 0.1 Fazekas points, p < 0.001). Greater WMH burden at baseline was associated with worse performance on all cognitive domains in both groups (p < 0.05). In the LLD group, the increase in WMH volume was significantly correlated with a decline in global cognition (r = -0.45, p < 0.001), executive function (r = -0.38, p = 0.003), and processing speed (r = -0.41, p = 0.001). Changes in depression severity were also correlated with WMH progression (r = 0.32, p = 0.012). Conclusion: This study provides evidence that WMH burden is significantly increased in LLD and that WMH progression contributes to cognitive decline and may exacerbate depressive symptoms over time. These findings highlight the importance of assessing and potentially targeting WMH in the management of LLD.